Aktivno zvijanje polimerov in filamentov - Flack, Ana (Matrika, 2017)
This article deals with twist dynamics of rotationally driven semi flexible polymers and filaments in a viscous fluid. The core of this article is a simple model that consist of uniform elastic rod that is forced to axially rotate about one fixed end and is free at the other end. At the beginning characteristic times and lengths for such motion are estimated. Through the principle of virtual work the derivation of equations for force and torque acting on such rod is explained. The meaning of equations of motion is examined and the critical frequency where twirling-whirling transition occurs is determined. Characteristic of motion after transition are presented with the help of numerical simulation results. To stress the importance of such dynamics an experiment that deals with motion of bacteria who change direction due to the instability of their flagella is reviewed.
Keywords: elastična palica; filamenti; filaments; polimeri; polymers; uniform elastic rod; viscous fluid; viskozna tekočina